(3TQM GddeYs - (3CHh GdbGSe YeQ Hf KGHJ GdKeGfjfi GdehUdjs; (3GHf Lfj , CHh GdaJM YKeGf Hf Lfj GdehUdj, GHf Lfj,J (B392 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CHh GdbGSe YeQ Hf KGHJ GdKeGfjfi GddZhi QMeg Gddg EYde Cf GdcdeI YfO Cgd GddZI JbY Ydi Gdbdjd hGdcHjQ jOdc Ydi Pdc bhdge PcQ adGf ai cdeJg s
(3BNQgG (B:s
(3hgPG GdbOQ GdPi PcQJg ai HGH GdEeGdI jSJOd Hg BNQ GdJYdjb Ydi GddeY s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3dgG fSNI CNQi eagQSI JMJ Qbe (B92 (3fMhs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs